دور البروجسترون في الوقاية من الولادة الباكرة - مرعي, رئيفة; الدالي, عصام; الحسن, هزار (Latakia University Journal -Medical Sciences Series, 2019)
الهدف من الدراسة: تقييم فعالية 17- هيدروكسي بروجسترون كابروات (OHPC -17) في خفض معدلات الولادة الباكرة في الحوامل عاليات الخطورة ممن لديهن قصة ولادة باكرة سابقة . شملت الدراسة 80 حامل ممن لديهن قصة ولادة باكرة سابقة، تم تقسيمهم إلى مجموعتين : المجموعةالأولى: ضمت 50 حامل تم إعطاؤهن حقن البروجسترون 250 ملغ أسبوعياً بدءاً من عمر ( 16-20) أسبوع وحتى بلوغ (36 )أسبوع أو حتى الولادة. المجموعة الثانية: ضمت 30 حامل لم يعطين الدواء. فوجدنا انخفاض واضح في معدل حدوث نكس الولادة الباكرة في المجموعة الأولى 28% مقارنة بالمجموعة الثانية 43.3%. كما أن الانخفاض في معدل حدوث نكس الولادة الباكرة تم ملاحظته بعمر حملي أقل من(32.35.37) أسبوع في المجموعة الأولى (28%, 14%, 6%) مقارنة بالمجموعة الثانية (43.3%، 23.3%، 13.3%) على الترتيب. The objective of this study is to evaluate the effectiveness of prophylactic use of 17- OHPC in preventing recurrent preterm delivery in women with a documented history of a previous spontaneous preterm birth. This study includes 80 pregnant women divided into two groups: The first includes 50 pregnant women receiving weekly 17- OHPC injections (250mg) from( 16-20) weeks up to 36weeks or delivery. The second group included 30 pregnant women receiving progesterone. We find that the recurrence of preterm birth is significantly less for women treated with17- OHPC (28%) compared to those (43.3%)who have not been treated. Women in the second group are significantly more likely to have spontaneous recurrent preterm birth at( <37,<35,<32) weeks of gestation (43.3%,23.3%,13.3%) compared to women who receive progesterone ( 28%,14%, 28%).